Quality of Work Life, Job Enrichment and their Impact on Employee Retention: Exploratory Research in Private Colleges in Baghdad - Ahmed M.M.; Khudari M.; Hussein A.M.; Jais J. (World Scientific and Engineering Academy and Society, 2024)
Quality of work life (QWL) can be impacted by a variety of factors, including organizational structure, the physical environment, job security, and the opportunity for personal growth and development. As job enrichment is a key component of QWL, it can play an important role in employee retention. The main objective of this research is to determine the dimensions of QWL and job enrichment that promote employee retention and how those dimensions significantly impact employee retention. The research was based on a questionnaire survey with (358) faculty members representing 10 private colleges in Baghdad, the questionnaires reliability and validity were examined, and data were described and analysed using a descriptive and analytical approach by using SmartPLS to test the hypothesises. The findings assert both quality of working life and job enrichment had a significant impact on employee retention. The study urges employers to offer highly desirable working conditions, and by utilizing a job enrichment strategy, faculty staff roles are created to keep them. 2023, World Scientific and Engineering Academy and Society. All rights reserved.